Regional brain glucose metabolism and gray matter volumetry for the evaluation of chronic traumatic encephalopathy in retired male soccer players: An [18F]FDG‐PET/MRI study: Neuroimaging / multi‐modal comparisons. (7th December 2020) - Aranha, Mateus Rozalem; Coutinho, Artur M; Carneiro, Camila de Godoi; Neto, Adalberto Studart; Tsunemi, Miriam; Moreira, Everton Luis Santos; Ianof, Jessica N; Anghinah, Renato; Nitrini, Ricardo; Cerri, Giovanni Guido; Fortea, Juan; Buchpiguel, Carlos A; et al.
Abstract: Background: Chronic traumatic encephalopathy (CTE) is a progressive tauopathy mostly described in military personnel, boxers and American football players. Soccer / European football players are also exposed to long‐term repetitive mild traumatic brain injuries (mTBI), which can lead to CTE. We hypothesized that retired soccer players may present with brain damage, as measured by regional brain glucose metabolism (rBGM) and gray matter (GM) volume in comparison to individuals without exposure to traumatic brain injury. We aim to evaluate rBGM measured with [18F]FDG‐PET, GM volume and the load of white matter lesions (WML) measured with MRI in a group of retired soccer players. Methods: This prospective study included 19 retired male soccer players (mean = 57, 6 years old) and 20 controls matched by age (mean = 60, 6 years old), submitted to brain MRI and [18F]FDG‐PET in a 3 Tesla SIGNA PET/MRI scanner (GE Healthcare) from January 2017 to September 2019. Assessment of rBGM, GM volume and load of WML were performed with the SPM8 software. Both groups were compared using the appropriate statistical tests available at SPM8 and R. The p‐value used for significance was 0.001, and correction for multiple comparisons was applied to the SPM analyses (pFWE/FDR< 0.05). Results: Retired soccer players presented with reduced rBGM in both temporal lobes, reaching statistical significance in left temporal pole and anterior aspect of left inferior temporal gyrus (pFWE/FDR<0.05). Reduction of grey matter volume were observed in similar regions, however with a lower extension, and without surviving correction for multiple comparisons (puncorrected<0.001). There were no differences between groups regarding WML. Conclusion: Our study shows a significant reduction in rGBM and less evident reduction in GM volume in the lateral and medial temporal lobes of retired soccer players in comparison to controls, which may be attributable to repetitive mTBI.